2011
DOI: 10.1021/ie200235e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feed Composition and Feed Impurities in the Catalytic Conversion of Syngas to Higher Alcohols over Alkali-Promoted Cobalt–Molybdenum Sulfide

Abstract: Alkali-promoted cobalt–molybdenum sulfide is a potential catalyst for the conversion of syngas into higher alcohols. This work is an investigation of how the feed composition influences the behavior of the sulfide catalyst. In a sulfur-free syngas the production of higher alcohols is observed to be optimal with an equimolar mixture of CO and H2 in the feed, while the methanol production benefits from an increasing hydrogen content in the feed. The influence of NH3 and H2O in the syngas feed has also been inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…A liquid feeding system, described in greater detail elsewhere [19], was used to supply the methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A liquid feeding system, described in greater detail elsewhere [19], was used to supply the methanol.…”
Section: Methodsmentioning
confidence: 99%
“…From experiments, Wantuck et al [42] reported a nonlinear Arrhenius behavior, with the rate constant increasing strongly above 600 K. However, their results have been questioned due to possible interference by thermal dissociation of CH 3 O (R19) at the higher temperatures. For this reason, Baulch et al [34] chose to disregard the data from Wantuck et al in their evaluation of k 19 . It is interesting to note that our theoretical rate constant (denoted by the solid line in Fig.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…22,23 Fig. 4 shows that the ratio of H 2 /CO rose rapidly when the oxygen concentration was increased.…”
Section: -7mentioning
confidence: 97%
“…The performance of catalysts for CO hydrogenation was evaluated in a fixed-bed continuous-flow reactor (detailed descriptions of the experimental set-up and the experimental procedure have been provided elsewhere) [58][59][60] with an online GC-FID/TCD detection system (6890N from Agilent Technologies). A bubble flow meter was used for the determination of volumetric flow rate of the reactor effluent.…”
Section: Catalyst Activity Testingmentioning
confidence: 99%